Strings in the η Carinae Nebula: Hypersonic Radiative Cosmic Bullets - Poludnenko, A. Y; Frank, A; Mitran, S (The Astrophysical journal, 2004)
We present the results of a numerical study focusing on the propagation of a hypersonic bullet subject to radiative cooling. Our goal is to explore the feasibility of such a model for the formation of "strings" observed in the eta Carinae Homunculus nebula. Our simulations were performed in cylindrical symmetry with the adaptive mesh refinement code AstroBEAR. The radiative cooling of the system was followed using the cooling curve described by Dalgarno and McCray. In this paper we discuss the evolution and overall morphology of the system as well as key kinematic properties. We find that radiative bullets can produce structures with properties similar to those of the eta Carinae strings, i.e. high length-to-width ratios and Hubble-type flows in the form of a linear velocity increase from the base of the wake to the bullet head. These features, along with the appearance of periodic "ringlike" structures, may also make this model applicable to other astrophysical systems such as planetary nebulae, e.g. CRL 618 and NGC 6543, young stellar objects, etc.